Effectiveness of socio-scientific issues with mind mapping strategy on students learning outcomes on heat topic - Adilliya Gerda Irananda; Laily Rosdiana (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2022)
This study aims to describe student learning outcomes in the knowledge aspect by implementing the socio-scientific issues method with a mind mapping strategy. The type of research uses a pre-experimental design with a one-group pretest-posttest design. The studied samples consisted of 32 students of grade eight junior high school SMP Negeri 14 Gresik, Indonesia. Data was collected using instruments in the form of learning implementation observation sheets, student response questionnaire sheets, and test assessments. The results of this study, namely: (1) the implementation of learning with the socio-scientific issues method with a mind mapping strategy at each stage got a very good category; (2) the application of the socio-scientific issues method with the mind mapping strategy received a very good response; (3) learning outcomes in the knowledge aspect showing an increase as evidenced by the N-gain average value in the high category.